Orca reproduction in captivity: A review of the science, ethics and welfare concerns - Dante McGillian (Annals of Marine Science - Peertechz Publications, 2023)
Orca whales, also known as killer whales, are highly social and intelligent animals that have captured the public's fascination for decades. However, the use of orca whales in marine parks and aquariums for human entertainment has sparked controversy about their welfare and ethical considerations. Captive breeding programs have been developed for several marine species, including orca whales, to ensure their survival. However, captive orca reproduction is a contentious topic due to the potential health and welfare concerns for the animals. In this scientific essay, we review the reproductive biology of orca whales in captivity, the health and welfare concerns associated with captivity, and the ethical considerations of keeping these intelligent and social animals in captivity for human entertainment. Our review highlights the need for continued research to improve the welfare of captive orcas and the conservation efforts of wild populations.